EDUKASI PENCEGAHAN COVID-19 DALAM MEDIA SOSIAL: GAMBARAN KONTEN VIDEO TIKTOK - Nur Shadrina Nasution; Syamsulhuda Budi Mustofa; Zahroh Shaluhiyah (Jurnal Kesehatan Masyarakat (Undip), 2021)
In the midst of the global pandemic of the corona virus (covid-19), social media consumption has increased significantly, one of which is the use of the Tiktok application. Tik Tok has partnered with a number of international organizations to share health information, this can be an opportunity for TikTok to be used as an educational medium with creative content. In this qualitative descriptive study, sampling was carried out using consecutive sampling, namely sampling by determining certain criteria to determine the research sample, there were 5 Tik Tok accounts that were used as research samples, namely @tanyadokter, @unicefindonesia, @alodokter, @halodocID and @dijkp in total. 55 videos. This research was studied using the theory of the SMCR communication model by Berlo, namely the process of delivering a message from source to receiver. The results showed that the types of messages uploaded by these accounts were mostly educational message types, namely as much as 29%. The most responses received by the @alodokter account were 144323 from the total likes, comments and shares campaigning for good and correct hand washing. From the results of the analysis of the video content of Tik Tok, it turns out that the use of the caption, hashtag, music / audio and filter effects features is very influential in increasing the number of responses. Using the Tik Tok application provides excellent new benefits, where users are provided with videos that match their preferences and needs accurately because the Tik Tok account that has been researched has collaborated with the World Health Organization and the Indonesian Ministry of Health so that the information provided has been preserved.